Toxic Metals and Subclinical Atherosclerosis in Carotid, Femoral, and Coronary Vascular Territories: The Aragon Workers Health Study. Issue 1 (9th December 2021) - Grau-Perez, Maria; Caballero-Mateos, Maria J.; Domingo-Relloso, Arce; Navas-Acien, Ana; Gomez-Ariza, Jose L.; Garcia-Barrera, Tamara; Leon-Latre, Montse; Soriano-Gil, Zoraida; Jarauta, Estibaliz; Cenarro, Ana; Moreno-Franco, Belen; Laclaustra, Martin; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Studies evaluating the association of metals with subclinical atherosclerosis are mostly limited to carotid arteries. We assessed individual and joint associations of nonessential metals exposure with subclinical atherosclerosis in 3 vascular territories. Approach and Results: One thousand eight hundred seventy-three Aragon Workers Health Study participants had urinary determinations of inorganic arsenic species, barium, cadmium, chromium, antimony, titanium, uranium, vanadium, and tungsten. Plaque presence in carotid and femoral arteries was determined by ultrasound. Coronary Agatston calcium score ≥1 was determined by computed tomography scan. Median arsenic, barium, cadmium, chromium, antimony, titanium, uranium, vanadium, and tungsten levels were 1.83, 1.98, 0.27, 1.18, 0.05, 9.8, 0.03, 0.66, and 0.23 μg/g creatinine, respectively. The adjusted odds ratio (95% CI) for subclinical atherosclerosis presence in at least one territory was 1.25 (1.03–1.51) for arsenic, 1.67 (1.22–2.29) for cadmium, and 1.26 (1.04–1.52) for titanium. These associations were driven by arsenic and cadmium in carotid, cadmium and titanium in femoral, and titanium in coronary territories and mostly remained after additional adjustment for the other relevant metals. Titanium, cadmium, and antimony also showed positive associations with alternative definitions of increased coronary calcium. Bayesian Kernel Machine Regression analysis simultaneously evaluating metal associations suggested an interaction between arsenic and the joint cadmium-titanium exposure. Conclusions: Our results support arsenic and cadmium and identify titanium and potentially antimony as atherosclerosis risk factors. Exposure reduction and mitigation interventions of these metals may decrease cardiovascular risk in individuals without clinical disease.